A Novel Approach to Identify and Prioritize the Connections Between Nature and People’s Well-Being in New Zealand - Ausseil, Anne-Gaëlle Elsa; Greenhalgh, Suzie; Booth, Pam; Lavorel, Sandra; Collins, Alison (Frontiers in Environmental Science, 2022)
Human well-being depends on the Earth’s natural system. While there is awareness of the impact of human activities on the environment, the reverse – nature’s role in human well-being – is usually not as clear. For decision makers and people to recognize the role of nature in human well-being, we need scientific evidence and ways to monitor trends that will ensure environmental policies are well designed and on track for long-term sustainability. We present a participative process to relate nature to human well-being and identify the important contributions from nature to different aspects of well-being. Our process is irrespective of classification systems for nature’s contributions and can use either ecosystem services or nature’s contributions to people (ES/NCP) concepts. Two criteria, impact and substitutability, have been used to rank the importance of the ES/NCP for well-being. We applied our approach in New Zealand, where the government has pioneered a well-being framework to measure wealth beyond GDP. The framework defines current well-being based on twelve domains, with intergenerational well-being dependent on four capitals (social, built, human and natural capital). By using a participative process, we designed a process to identify the important ES/NCP and well-being relationships. Our results showed that regulating ES/NCP contributed to the six broader categories of well-being, with non-material ES/NCP contributing to health, social relations, material well-being, and environmental quality categories. Material ES/NCP, such as food, energy, and timber, contributed mainly to material well-being, with small contributions to social relations and environmental quality well-being categories. This process can raise awareness and help stakeholders recognize the value of nature-based solutions for human well-being. It provides a structured approach to underpin fit-for-purpose indicators for monitoring and reporting the relationship between nature and well-being, target policy initiatives and identify potential trade-offs, and prioritize investment decisions across multiple outcomes.